Settlement of Disputes Regarding the Collision Incident Between a Philippine Civilian Supply Ship and a Chinese Coast Guard Vessel in the South China Sea in 2023 - Abdul Arif Putra; Atikah Rahmi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The South China Sea dispute has emerged as a highly complex issue, marked by various tensions that disrupt regional stability. The collision incident between Philippine and Chinese vessels has further heightened these tensions. This research aims to examine the legal implications of the collision between the Philippine and Chinese ships, to understand the dispute resolution mechanisms under the 1982 UNCLOS, and to assess the application of UNCLOS provisions in the collision incident between the Philippines and China in the South China Sea. The research method used is normative legal research with a case approach. The results indicate that China’s actions constitute a violation of provisions under international law. The impact of the collision incident has further exacerbated the contest over territorial claims in the South China Sea.